If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -10 = x + 4 Reorder the terms: -10 + 7x = x + 4 Reorder the terms: -10 + 7x = 4 + x Solving -10 + 7x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + 7x + -1x = 4 + x + -1x Combine like terms: 7x + -1x = 6x -10 + 6x = 4 + x + -1x Combine like terms: x + -1x = 0 -10 + 6x = 4 + 0 -10 + 6x = 4 Add '10' to each side of the equation. -10 + 10 + 6x = 4 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = 4 + 10 6x = 4 + 10 Combine like terms: 4 + 10 = 14 6x = 14 Divide each side by '6'. x = 2.333333333 Simplifying x = 2.333333333
| y+2=-3(-2)+8 | | c+6=-3 | | y+2=-3(0)+8 | | -3.1+x=-2.1 | | 6a-3=2 | | y+2=-3(2)+8 | | -3x(2x-3)=-5x+5 | | 6n+3=-2n+12 | | 6+3=3-3y | | -6(-2)+5=y | | 13+a=11 | | 125n^3-50n^2+100n-40= | | 1/2x-3y=-9 | | -6(0)+5=y | | 8(c-3)=96 | | -6(2)+5=y | | -2+4y=12 | | 35x^3+15x^2-49x-21= | | 356=72 | | 356=151872 | | 4m^2-20m+25= | | 3(-2)+3=3-y | | 3(0)+3=3-y | | 5t+15= | | 4-5(x-3)+2x=-2 | | 3(2)+3=3-y | | 4(-2)+2=y | | 4(0)+2=y | | 9z(3+2)=135 | | 4(d-3)=28 | | 4(2)+2=y | | 6x+11=-64-9 |